Serum C-Reactive Protein/Albumin Ratio and its Correlation with Disease Activity in Rheumatoid Arthritis Patients - Ammar Hatem Abdullateef; Zakaria M. Al-Ghazaly; Noor Hasan Baiee; Mohammed Ali Al-Jabory (Medical Journal of Babylon)
Background:Rheumatoid arthritis (RA) is an autoimmune disorder affecting joints with a progressive symmetric inflammation leading to bone erosion, cartilage destruction and disability. Usually, RA activity is measured by using RA Score of Disease Activity involving 28-joint count (DAS-28). C-reactive protein (CRP) to albumin ratio (CAR) has been recently used as a new indicator to assess inflammation and predict prognosis of certain malignancies with Some studies demonstrated its correlation with disease activity of some inflammatory diseases, particularly Crohn’s disease and RA. Objectives:to assess the role of serum C-reactive protein to albumin ratio (CAR) in RA as a marker for activity of this disease. Materials and Methods:This cross-sectional study included 84 RA patients. Each patient was tested for albumin and CRP in addition to erythrocyte sedimentation rate (ESR). CAR was calculated mathematically by dividing CRP on albumin value. RA activity was assessed by applying DAS-28-ESR scoring system. Results:The mean of CAR was 4.25. Significant correlation was found between CAR and DAS-28 CRP disease activity index, CRP, ESR and patient VAS and serum albumin. CAR was showing significant differences among high, medium and low-remission groups of disease activity. However, positive but nonsignificant correlation was found between CAR and the DAS-28-ESR disease activity scoring system, CDAI and the physician VAS. Conclusion:CAR, can be considered as useful initial simple investigation which can give an idea about degree of disease activity and the need for further evaluation and management with less time, cost and effort especially in areas with low medical resources and facilities.